Prophylactic efficacy of Lactobacillus curvatus B67-derived postbiotic and quercetin, separately and combined, against Listeria monocytogenes and Salmonella enterica ser. Typhimurium on processed meat sausage - Toushik, Sazzad Hossen; Kim, Kyeongjun; Park, Sang-Hyeok; Park, Jun-Ha; Ashrafudoulla, Md; Ulrich, Mevo Senakpon Isaie; Mizan, Md. Furkanur Rahman; Hossain, Md. Iqbal; Shim, Won-Bo; Kang, Iksoon; Ha, Sang-Do (Meat science, 2023)
This study investigated the antimicrobial and antibiofilm efficacy of separate and combined treatments of Lactobacillus curvatus B67-produced postbiotic and the polyphenolic flavanol quercetin against Listeria monocytogenes and Salmonella enterica ser. Typhimurium. The antimicrobial potentiality of the postbiotic was chiefly associated with organic acids (e.g., lactic and acetic acids). At sub-minimum inhibitory concentration (1/2 MIC), the postbiotic and quercetin effectively reduced the pathogenic biofilm cells on processed pork sausage and meat-processing surfaces (e.g., stainless-steel and rubber). Moreover, the postbiotic exhibited strong residual antimicrobial efficacy over diverse pH and temperature ranges. In addition, the combination of postbiotic with quercetin increased the leakage of pathogenic intracellular metabolites (e.g., nucleic acids and protein) and inhibited pathogenic biofilm formation on both biotic and abiotic surfaces. Therefore, this study confirmed that lactic acid bacteria-derived postbiotic and plant-derived quercetin could be used as potential alternative bioprotective agents in the meat processing industry. •Lactobacillus curvatus B67-produced bioactive soluble byproducts as postbiotic.•Postbiotic exhibited broad pH (1–6) and temperature (40–121 °C) stability.•Postbiotic and quercetin showed antibiofilm action on sausage and abiotic surfaces.•Combining postbiotic with quercetin enhanced their biocidal activity.•Both postbiotic and quercetin act as bioprotective agents in the meat industry.